Negative life events and migraine: a cross-sectional analysis of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) baseline data - Santos, Itamar S (BioMed Central, 2014)
BACKGROUND: Stress is a typical migraine trigger. However, the impact of negative life events on migraine activity is poorly studied. The aim of this study is to investigate the association between negative life events and migraine using data from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) baseline assessment. METHODS: ELSA-Brasil is a multicenter cohort study conducted in six Brazilian cities. Baseline assessment included validated questionnaires for headache classification and the occurrence of five pre-specified negative life events (financial hardship, hospitalization other than for childbirth, death of a close relative, robbery and end of a love relationship), focusing on a 12-month period before evaluation. We built crude and adjusted logistic regression models to study the association between the occurrences of negative life events and migraine diagnosis and activity. RESULTS: We included 4,409 individuals with migraine and 4,457 participants without headache (reference). After adjustment for age, sex, race, income and educational level, we found that the occurrence of a negative life event (Odds ratio = 1.31; 95% confidence interval = 1.19 – 1.45) was associated with migraine. However, after stratifying with subgroup analyses, only financial hardship (Odds ratio = 1.65; 95% confidence interval = 1.47 – 1.87) and hospitalization (Odds ratio = 1.47; 95% confidence interval = 1.25 – 1.72) were independently associated with migraine. Further adjustment for a current major depression episode and report of religious activity did not significantly change the results. Considering migraine frequency as (a) less than once per month, (b) once per month to once per week, or (c) more than once per week, financial hardship and hospitalization remained significantly associated with migraine in all episode frequency strata, with higher odds ratios for higher frequencies in adjusted models. We also observed a significant association between the death of a close relative and the highest migraine frequency stratum (Odds ratio = 1.38; 95% confidence interval = 1.09 – 1.75) in full-adjusted model. CONCLUSIONS: The occurrence of financial hardship and hospitalization had a direct and independent association with migraine diagnosis and frequency. The death of a close relative was also independently associated with the highest migraine frequency stratum.